Multi-omics assessment of gut microbiota in circadian rhythm disorders: a cross-sectional clinical study - Tian, Yuting; Zhao, Rong; Xiao, Shili; Chen, Lu; Cheng, Yi; Meng, Wei; Tang, Zongyuan; Cai, Yi; Xiao, Zhifeng; Yi, Ailin; Chen, Minjia; Zhao, Xuefei; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundThe interaction between the host and microbiota is influenced by host circadian rhythm. However, it is unknown what the changes of gut microbiota and metabolites.MethodsWe conducted a cross-sectional study (n=72) in which participants’ fecal DNA was detected by macrogenomic sequencing analysis. The feces, urine and blood were analyzed by widely targeted metabolomics analysis.ResultsPearson correlation analysis showed that most of the clinical symptoms of people with circadian rhythm disorders were moderately positively correlated with gastrointestinal symptoms. By distilling the results of multinomic analysis, we reported a variety of different species (19 species in the gut) and metabolites. In our results, the correlation of multiomics is mostly concentrated in Lachnospiraceae bacterium and Streptococcus mitis oralis pneumoniae. Bile acid-related metabolites are the most significant metabolites associated with these species.DiscussionOur study demonstrates the severity of clinical manifestations caused by circadian rhythm disorder is closely related to microbiota and metabolism. In the future, personalized interventions targeting specific microbial species or metabolites may help alleviate the physical and psychological discomfort induced by circadian rhythm disturbances.